Flash-in-the-pan development in Egypt? IMF-backed economic recovery stymied by absence of structural reforms and massive human rights violations - Stephan Roll (Stiftung Wissenschaft und Politik (SWP), 2018)
In November 2016, Egypt agreed a comprehensive aid programme with the International Monetary Fund (IMF). Its stated objective was to stabilize the country's macroeconomic situation within three years and put it on track for inclusive economic growth. At the half-way stage, hardly any structural reforms have been implemented despite a short-term macroeconomic stabilization resulting from the conditions put in place. Rather, the increasingly influential military has prevented the emergence of a functioning market economy. This has been compounded by the disastrous human rights record of the government under President Abdel Fattah el-Sisi, which has also had a negative impact on Egypt's economic development. Germany played a key role in the IMF agreement being concluded. The German government should, therefore, work to ensure the IMF produces a critical assessment of the reforms that have taken place so far. It should also link its willingness to support future aid packages with improving the human rights situation and strengthening civil society.
Keywords: 320